The Prices of Investment Goods and the Volume of Production in the United States - Goris, Hendrieke; Koyck, Leen M. (The Review of Economics and Statistics, 1953)
AN insight into the problem of the fluctuations of iron and steel prices or, generally, of the prices of investment goods, is important with regard to the part these prices play in the relation between saving and investment. A change in the prices of investment goods will in general affect the physical volume of investment as well as the amount of money savings which is absorbed by investment activity. The influence of these prices on the volume of investment might not be very large (several investigations seem to point in that direction), but even if that were the case the influence of a price change on the amount of savings that is absorbed by investment activity will be important. In this paper our attention will be concentrated exclusively on the way prices of investment goods are fixed by the producers, more specifically on the relation between the volume of production of investment goods and the prices of these goods (the price flexibility). As the best available figures are for the United States, we tested the influence of changes in the percentage of capacity used upon prices of investment goods on the basis of United States data. i. Tinbergen's analysis. The starting point for our investigations was the explanation of price fluctuations of investment goods given by Tinbergen in his League of Nations publication, Business Cycles in the U.S.A. I9I9-32. In his price-determination equation ' Tinbergen explains prices of investment goods by the following factors: (a) the variable costs per unit of product, represented by the wage rate, (b) the volume of production of investment goods, and (c) a trend factor. The purpose of this paper is to extend Tinbergen's analysis in some aspects. In the first place more observations are available now. Tinbergen's book covers the period I9I9-32, while our analysis is based on figures for the period I9I9-40. There is still another difference between our investigation and Tinbergen's. We were especially interested in finding examples of bottlenecks. As we could not detect any influence of bottlenecks on the price movement of finished investment goods, we went back a little on the way from raw material to final product, and investigated the prices of iron and steel, as the chance of finding nonlinear relations becomes larger when the products investigated approach raw materials more closely. With regard to the factor mentioned under (a) Tinbergen says: we are considering all enterprises, which are here regarded as being vertically amalgamated, practically the only element in variable cost will be variable labour cost. Its influence on price may be estimated on a priori grounds, which in general seem safer than any other basis. Labour costs may be estimated at about 50% of prices of investment goods. This does not correspond, however, to direct labour only but to all labour. From the figures of the Federal Reserve Board it may moreover be estimated that a io% increase in production of durable goods is accompanied by a 7% increase in hours of work. Marginal labour-costs seem therefore to be about seventenths of average labour-costs for average production. The price increase, corresponding to a 1o% increase in wages, will therefore, in the short run, be equal to 5 X 0.7% = 3.5%. (Italics are ours.) For reasons to be mentioned afterward we shall use unit labor cost and not the wage rate as an explanatory variable, deviating from Tinbergen in this respect. 2. Changes in labor costs and prices. Since Tinbergen's study our knowledge of the influence of changes in labor costs on prices has been considerably extended by Leontief.2 The statistical material presented in his papers there'A price-determination equation is a relation that tells what factors influence the decisions of producers or sellers with regard to the prices to be fixed. This relation contains the same variables as a supply relation, but price is an effect rather than a cause and may therefore be lagged behind quantities and supply factors. 2 W. Leontief, Wages, Profits, and Prices, Quarterly Journal of Economics, I946-47, p. 26.